Therapeutic targets for lung cancer: genome-wide Mendelian randomization and colocalization analyses - Luan, Yi; Xian, Desheng; Zhao, Changwen; Qing, Xin; He, Hanlin; Zheng, Kaixuan; Song, Wenjun; Jiang, Taijiao; Wang, Wenjian; Duan, Chaohui (Frontiers in Pharmacology, 2024)
Background: Lung cancer, categorized into non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC), remains a significant global health challenge. The development of drug resistance and the heterogeneity of the disease necessitate the identification of novel therapeutic targets to improve patient outcomes. Methods: We conducted a genome-wide Mendelian randomization (MR) and colocalization analysis using a comprehensive dataset of 4,302 druggable genes and cis-expressed quantitative trait loci (cis-eQTLs) from 31,884 blood samples. The study integrated genomic analysis with eQTL data to identify key genes associated with lung cancer risk. Results: The analysis revealed five actionable therapeutic targets for NSCLC, including LTB4R, LTBP4, MPI, PSMA4, and TCN2. Notably, PSMA4 demonstrated a strong association with both NSCLC and SCLC risks, with odds ratios of 3.168 and 3.183, respectively. Colocalization analysis indicated a shared genetic etiology between these gene expressions and lung cancer risk. Conclusion: Our findings contribute to precision medicine by identifying druggable targets that may be exploited for subtype-specific lung cancer therapies.